Uncertainty in the Future Distribution of Tropospheric Ozone over West Africa due to Variability in Anthropogenic Emissions Estimates between 2025 and 2050 - J. E. Williams; P. F. J. van Velthoven (International Journal of Geophysics)
Particle and trace gas emissions due to anthropogenic activity are expected to increase significantly in West Africa over the next few decades due to rising population and more energy intensive lifestyles. Here we perform 3D global chemistry-transport model calculations for 2025 and 2050 using both a “business-as-usual” (A1B) and “clean economy” (B1) future anthropogenic emission scenario to focus on the changes in the distribution and uncertainties associated with tropospheric O3 due to the various projected emission scenarios. When compared to the present-day troposphere we find that there are significant increases in tropospheric O3 for the A1B emission scenario, with the largest increases being located in the lower troposphere near the source regions and into the Sahel around 15–20°N. In part this increase is due to more efficient NOx re-cycling related to increases in the background methane concentrations. Examining the uncertainty across different emission inventories reveals that there is an associated uncertainty of up to ~20% in the predicted increases at 2025 and 2050. For the upper troposphere, where increases in O3 have a more pronounced impact on radiative forcing, the uncertainty is influenced by transport of O3 rich air from Asia on the Tropical Easterly Jet.